GAMBARAN TINGKAT PENGETAHUAN SISWA SEKOLAH MENENGAH KEJURUAN TENTANG BUSINESS MODEL CANVAS DALAM ANALISIS BISNIS - Priyo Legowo, Wahyu; Revika Rachmaniar; Pupung Ismayadi; Yola Desnera Putri; Rival Ferdiansyah (Jurnal Pengabdian Masyarakat (Jupemas), 2025)
Limited knowledge of business design frameworks poses a challenge for vocational high school (SMK) graduates who plan to start their own businesses. This study aims to enhance the understanding of pharmacy vocational students regarding the Business Model Canvas (BMC) as a business analysis tool. The activity involved 62 students as respondents and employed questionnaires to measure their level of knowledge before and after the intervention. The program began with the delivery of materials on the fundamental concepts of BMC, covering key components such as value propositions, customer segments, and key activities. Subsequently, the students engaged in discussions and practical exercises to develop BMCs based on case studies relevant to the pharmaceutical field. The results indicated that, prior to the program, most students had limited understanding of the elements within the BMC. After the explanation and practice sessions, students demonstrated improved comprehension in creating structured and applicable BMC designs. This activity is expected to serve as an initial step in equipping pharmacy vocational students with essential business planning skills to support their preparedness for entrepreneurship in a competitive era.